O Pełzaniu i Pełzarce - Madejski, J. (Engineering Transactions, 1956)
This paper contains a theory of long-time tensile test of materials on a vertical machine. The following two cases of materials were investigated:(1) a test piece preserving more or less constant area of cross-section,(2) a very ductile material with a considerable reduction in cross-sectional area before fracture.The presented theory of creep is based on relaxation, as this effect is much less influenced by the dynamics of the testing machine. It has been shown that the true creep curve is distorted by the vibrations of testing machinery; because of the clearances in machine bearings these vibrations cause a series of blows having a very large frequency. This is the reason why the nonlinear part of the creep curve cannot be used in the computation of rheological characteristics of materials. For this purpose, only the linear stage of creep may be applied. Some materials show the effect of growth of creep rate before fracture of the test piece occurs, the reason for this being in the reduction of cross-sectional area of the test piece.